Penerapan Arsitektur Hijau dengan Menggunakan Material Bekas Rumah Botol Ir. Ridwan Kamil - Halimatussa’diyah; Nur A’siyah Jamil Sarumpaet (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Green architecture is one way to create a house or building that is environmentally friendly. One element that can be applied to realize green architecture is by making efficient use of recycled materials and development efforts by paying attention to good environmental carrying capacity, namely the use of used materials can be one solution to overcome sustainability problems. One reaction to the environmental crisis is the emergence of the concept of green architecture or green architecture which leads to sustainable design and awareness of energy and ecology in managing an environment. This study examines the application of green architecture in the residence of architect Ridwan Kamil known as the Bottle House. The Bottle House is a house that is designed to have a balanced reciprocal relationship with its environment. The use of used bottles is one design idea that helps reduce waste in Indonesia and can also be an alternative material that is not only functional but also aesthetic. Creatively, the bottle house shows how art and design can influence people's mindsets.